The reduction of serum aminotransferase levels is proportional to the decline of the glomerular filtration rate in patients with chronic kidney disease (Clinics, 2015)
OBJECTIVE: This study sought to determine the serum aminotransferase levels of patients with predialysis chronic kidney disease and establish their relationships with serum creatinine levels and glomerular filtration rate. METHODS: Patients with chronic kidney disease were evaluated between September 2011 and May 2012. Aminotransferase and creatinine serum levels were measured using an automated kinetic method, and glomerular filtration rates were estimated using the Cockroft-Gault and Modification of Diet in Renal Disease formulas to classify patients into chronic kidney disease stages. RESULTS: Exactly 142 patients were evaluated (mean age: 64±16 years). The mean creatinine serum level and glomerular filtration rate were 3.3±1.2 mg/dL and 29.1±13 mL/min/1.73 m2, respectively. Patients were distributed according to their chronic kidney disease stages as follows: 3 (2.1%) patients were Stage 2; 54 (38%) were Stage 3; 70 (49.3%) were Stage 4; and 15 (10.5%) were Stage 5. The mean aspartate aminotransferase and alanine aminotransferase serum levels showed a reduction in proportion to the increase in creatinine levels (p=0.001 and p=0.05, respectively) and the decrease in glomerular filtration rate (p=0.007 and p=0.028, respectively). Alanine aminotransferase and aspartate aminotransferase serum levels tended to be higher among patients classified as stage 2 or 3 compared with those classified as stage 4 or 5 (p=0.08 and p=0.06, respectively). CONCLUSIONS: The aspartate aminotransferase and alanine aminotransferase serum levels of patients with predialysis chronic kidney disease decreased in proportion to the progression of the disease; they were negatively correlated with creatinine levels and directly correlated with glomerular filtration rate.